Crystal Forms of the Antihypertensive Drug Irbesartan: A Crystallographic, Spectroscopic, and Hirshfeld Surface Analysis Investigation - Araya Sibaja, Andrea Mariela (2022)
The design of new pharmaceutical solids with improved physical and chemical properties can be reached through in-detail knowledge of the noncovalent intermolecular interactions between the molecules in the context of crystal packing. Although crystallization from solutions is well-known for obtaining new solids, the effect of some variables on crystallization is not yet thoroughly understood. Among these variables, solvents are noteworthy. In this context, the present study aimed to investigate the effect of ethanol (EtOH), acetonitrile (MeCN), and acetone (ACTN) on obtaining irbesartan (IBS) crystal forms with 2,3-dibromosuccinic acid. Crystal structures were solved by single-crystal diffraction, and the intermolecular interactions were analyzed using the Hirshfeld surfaces analysis. The characterization of physicochemical properties was carried out by powder X-ray diffraction, Fourier transform infrared spectroscopy (FT-IR), thermal analysis, and solution-state NMR techniques. Two different IBS salts were obtained, one from MeCN and ACTN (compound 1) and a different one from EtOH (compound 2). The experimental results were in agreement with the findings obtained through quantum mechanics continuum solvation models. Compound 1 crystallized as a monoclinic system P21/c, whereas compound 2 in a triclinic system P1̅. In both structures, a net of strong hydrogen bonds is present, and their existence was confirmed by the FT-IR results. In addition, the IBS cation acts as a H-bond donor through the N1 and N6 nitrogen atoms which interact with the bromide anion and the water molecule O1W in compound 1. Meanwhile, N1 and N6 nitrogen atoms interact with the oxygen atoms provided by two symmetry-related 2,3-dibromo succinate anions in compound 2. Solution-state NMR data agreed with the protonation of the imidazolone ring in the crystal structure of compound 1. Both salts presented a different thermal behavior not only in melting temperature but also in thermal stability.